Continence outcome following needle less operation (vaginal approach) using indigenous mesh - Goyal, Neelam; Goyal, Sanjay Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Economical and accessible non-extensive operation for stress incontinence in women who cannot afford expensive cost of mesh available for mini arc operation and other surgery of incontinences. Inexpensive hernial mesh (Hinglact), commonly available was used after indigenously designing it and placing it without a needle, under the Posterior urethral fascia with a single small vaginal incision. Methods: The present study was conducted on 25 female patients of post-menopausal group who presented with pure stress incontinence complaints. These patients did not have any uterine descent or previous surgery. Indigenously designed hernia mesh used in place of expensive needled Incontinence Meshes available by a single small incision in posterior urethera area. Results: Nearly 75% women with stress Incontinence were relieved of their symptoms with this inexpensive mesh without a needle. Conclusions: Very effective, inexpensive mesh and surgical procedure for poor socio economic, group of women found to relieve significant Incontinent patients compared to commonly used mesh with a needle.